A meta-analysis on the effects of exercise training on the VO2max in children and adolescents (Meta análisis de los efectos del entrenamiento en el VO2máx en niños y adolescentes) - Pedro Carazo-Vargas; José Moncada-Jiménez (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The chronic adaptations of the cardiovascular system to exercise training in children and adolescents yield inconclusive results, in spite of previous meta-analytic evidence. The aim of this meta-analysis was to determine the effectiveness of exercise training on the VO2max of children and adolescents. The studies meta-analyzed met the following inclusion criteria: a) healthy individuals, b) participants between 10 and 18 years old, c) being trained in some type of supervised exercise program, d) VO2max reported in ml·kg-1·min-1, e) the study reported before and after mean and standard deviation, f) pre-test post-test research designs, and g) the study was published in a peer-reviewed journal up to February, 2013. Thirty-four studies and 96 effect sizes (ES) were obtained. Compared to controls, experimental groups showed a significant improvement in VO2max (p < 0.01) following exercise training. The increase in VO2max was maintained regardless of the sample size characteristics and the exercise protocol. Based on the findings of this study, in order for children and adolescents to improve their VO2max, exercise training should include at least two sessions per week of > 20 minutes duration per session, performed at a moderate intensity. In summary, planned exercise training improves VO2max in children and adolescents. Key words. VO2max, aerobic power, training, children, adolescents, meta-analysis.